The effect of assembly design parameters on assembly time - Saptari, Adi; Sylvester Sabuk, Precilla; Halim, Isa; Mohamad, Effendi; Salleh, Mohd Rizal (Penerbit Universiti Teknikal Malaysia Melaka, 2015)
Reducing cycle time has an impact in many aspects such as productivity and capacity of industry. This study investigates the effect of assembly design parameters such as workstation design, working posture: standing and sitting and jig design on plug assembly time. The parameters or factors involved were three jig designs; number of holders, working postures: standing and sitting to assembly time and gender. An experiment with a full factorial design with four factors of 2 and 3 levels was applied. Ten participants consisting of five males and fives females were asked to assemble the plugs. The study concluded that all main factors, and some interaction factors significantly contributed to assembly time. The lowest assembly time per plug for assembly setting was sitting posture by male operators , using rectangular jig with 3 holders per jig. Meanwhile the highest assembly time per plug was performed by the female operator using horizontal jig with 5 plugs holder per jig. The study also generates the regression model that describes the relationship of all factors involved. Validation of the model also was performed by taking some runs of experiments. The average deviation of actual data and predicted is less than five per cent.